Analysis of Eddy Current Generation on the Juno Spacecraft in Jupiter's Magnetosphere. Issue 7 (15th July 2020) - Kotsiaros, S.; Connerney, J. E. P.; Martos, Y. M.
Abstract: The Juno mission to Jupiter, in polar orbit around the gas giant since 4 July 2016, samples the planet's environment with dedicated particle and fields instruments. Juno's magnetometer investigation employs a pair of boom‐mounted vector fluxgate magnetometers colocated with a set of star cameras to map Jupiter's magnetic field with high accuracy. Juno is a spinning spacecraft, rotating at approximately two rotations per minute. In strong magnetic field environments experienced near periapsis, Eddy currents are generated within electrically conductive material near the magnetic sensors. These currents adversely affect measurements of the environment, most evident in the appearance of a spin modulation in the field magnitude. We demonstrate, by finite element modeling and laboratory measurements, that the spin modulation is caused by a physical signal due to Eddy currents generated by the rotation of the conductive spacecraft structure in the presence of a strong magnetic field. We present a finite element model of the induced field and develop a matrix method for removing the Eddy current contribution to the measured field. Juno magnetic field measurements in strong fields are corrected for Eddy current contributions using this model of the interaction. Key Points: Juno's passages through Jupiter's strong magnetic field revealed an unexpected spin modulation in the magnitude of the magnetic field Rotation of the spacecraft in strong magnetic fields results in the generation of Eddy currents within the spacecraft's conductive structure The magnetic field due to Eddy currents is well described by a finite element model, the predictions of which are in remarkable agreement with the measured signals